Effects of fuel injection strategy and ammonia energy ratio on combustion and emissions of ammonia-diesel dual-fuel engine. (1st June 2023) - Jin, Shouying; Wu, Binyang; Zi, Zhenyuan; Yang, Puze; Shi, Taifeng; Zhang, Junhong
Highlights: As the ammonia energy ratio increased from 0% to 90%, the combustion continued to deteriorate. Ammonia inhibited the dehydrogenation process in the low-temperature reaction stage of diesel, and the pathway of OH production was altered. The formation pathway and reaction conditions of NO x and N2 O were revealed. Pre-injected diesel can improve the activity of the mixture and reduce greenhouse gas emissions while achieving high thermal efficiency. Abstract: As the greenhouse effect continues to intensify, ammonia, a carbon-free fuel, is gradually gaining attention. The ammonia-diesel dual-fuel (ADDF) engine can effectively overcome the disadvantages of high auto-ignition temperature and slow flame speed of ammonia, which is an effective way to reduce greenhouse gas (GHG). Aiming at achieving high thermal efficiency and low emissions of ADDF engine, the effects of ammonia energy ratio (AER) and injection strategy on combustion and emission characteristics were studied by combining experimental and simulation results. It was found that as the AER increased from 0 % to 90 %, the gross indicated thermal efficiency (ITEg) decreased continuously. Due to the slow flame speed of ammonia and the inhibition of the dehydrogenation process during the low temperature reaction of diesel, the emission of unburned ammonia increased significantly, reaching 31 g/kwh under the condition of 50 % AER. Improving the combustion efficiency of ammonia and reducing the emission of unburned ammonia were the keys to improving the ITEg of ADDF engine. Amino groups have a denitrification effect, and nitric oxide (NO) can be reduced to more stable nitrogen (N2 ). Therefore, NO emissions decreased when the AER increased. The production and consumption of nitrous oxide (N2 O) were influenced by temperature, and its production region was mainly the low temperature region where the reaction of ammonia occurred, while N2 O was reduced to N2 at high temperature conditions. As the AER increased, the deterioration of N2 O emissions was not conducive to reducing GHG. The double injection strategy can significantly improve the activity of the mixture, accelerate combustion, reduce unburned ammonia emissions and incomplete combustion losses. By optimizing the injection strategy and regulating the combustion process, an ITEg of 49.18 % can be achieved when the AER was 50 %, and GHG can be reduced by 14.2 %.